On Identification of Economic Systems - Galstyan, Gagik (Journal of Sociology: Bulletin of Yerevan University, 2017)
Historical development of mankind is divided into certain periods. Yet in the economic science, there is no accepted and unified approach concerning the periodization of economic growth and development. In the present article, a comparison of the approaches to such divisions is presented with the aim of more exact diagnostics of the post-socialistic economic structures.
Keywords: economic system, periodization, productive forces, socio-economic formation, stages of economic growth, economic structure